The Relationship Between the Type and Central Slope of the Fixation Disparity Curve and Symptoms - Yekta, A.A.; Pickwell, L.D.; Jenkins, T.C.A. (Canadian Journal of Optometry, 2026)
A modified near Mallett unit was used for generating forced vergence fixation disparity curves in 84 symptomatic and 50 symptom-free patients. The central slope of the curves was calculated for each patient. No significant difference was found between the symptomatic and symptom-free groups with respect to the type and central slope of the curves.